Condiciones ergonómicas-ambientales y su incidencia en la agudeza visual en los trabajadores de 30-55 años del Distrito de Salud Vinces-Los Ríos en el periodo diciembre-mayo 2023. - Astudillo Maridueña, Raquel Ivonne (2023)
The investigative study was developed with a non-experimental, descriptive, and observational investigative methodology, which adjusted to the profile that characterizes our research topic that deals with Ergonomic-Environmental and Visual conditions and its incidence in Visual Acuity in workers of 20 -30 years of the Vinces-Los Ríos Health District. All this with the aim of knowing how these ergonomic conditions affect and which are the ones that most affect the work environment and if this ergonomics are met a priori in the institution and above all what are the affectations that these have developed in the visual acuity of the chosen population. All the information collected has been quantified and tabulated using computer programs such as Excel and interpreted in Microsoft Word, with which we have the following results, always subject to the stated objectives: that within visual disorders such as myopia there is a predominance in 15 of the 32 women representing 47% and 5 of 12 men 42%, giving a total of 20 people, which would be almost 50% of our population, where myopia is the highest rate among the work staff, the symptom that most suffered by workers is tearing, which represented 34%, that the ergonomic factor that most affects their visual acuity is light with 27%, that 75% of the work personnel have not seen an optometrist and that if there is poor performance related to these optical problems in office number 1 there is 29%, in office 2 29%, in office 3 29% and in office 4 13%. It is recommended that managers carry out a study of the facilities so that the parameters established for an implementation of adequate ergonomics are met, to safeguard the integrity of their workers and improve and raise their work performance.